The presence of toxic metals in popular farmed fish species and estimation of health risks through their consumption - Resma, Nighat S.; Meaze, A.K.M. M. H.; Hossain, S.; Khandaker, Mayeen Uddin *; Kamal, M.; Deb, N. (Elsevier, 2020)
This study concerns an assessment of essential and toxic metals (Zn, Cu, As, Cr and Cd) in some popular farm fishes which are largely consumed by the populations of the Southern region in Bangladesh. Three different species of fish (T. nilotica, P. pangasius and L. rohita) were collected from four representative farms located in the Fatickchari, Hathazari, Patiya and Raozan Upazila of Chittagong district. Flame Atomic Absorption Spectrometer (FAAS) and Graphite Furnace Atomic Absorption Spectrometer (GFAAS) were used to measure the metal concentrations. The order of concentration of metals in flesh was Zn > Cu > Cr > As > Cd with values of 16.205 +/- 0.303 > 0.874 +/- 0.037 > 0.590 +/- 0.05 >0.042 +/- 0.003 > 0.004 +/- 0.00 (mg/kg dw) in T. nilotica, 20.324 +/- 0.697 > 1.035 +/- 0.050> 0.577 +/- 0.074> 0.045 +/- 0.005 > 0.006 +/- 0.000 (mg/kg dw) in P. pangasius and 22.270 +/- 0.745 > 0.953 +/- 0.525 > 0.623 +/- 0.060 > 0.035 +/- 0.002 > 0.004 +/- 0.000 (mg/kg dw) in L. rohita. Measured data lie within the permissible limits recommended by WHO/FAO. Potential metal toxicity to human health following the consumption of the studied fishes was estimated via a number of hazard parameters: Daily intake of metal (DIM), Target hazard quotient (THQ), Hazard index (HI) and Target risk (TR), all of the data show values within the recommended level given by regulatory bodies. Estimated TR for potential carcinogenic metals As, Cr and Cd were found in the range (10_6 - 10_5), which lies within the US-EPA risk range of 10_6 - 10_4. Note that, fish consumption forms a minor part of the total diet while the US-EPA risk range is for the dietary intake from all foods. Therefore the estimated risk may not be totally neglected. Moreover, considering the non-biodegradability of toxic metals and their potential uptake in fish tissues, reduction in metal supplementation in fish feed should be introduced and periodic monitoring of fish may help to mitigate non-essential metal toxicity to consumers.